Pemantapan mutu dan mutu hasil analisis laboratorium kimia klinik swasta di Kalimantan Selatan = Quality control and quality of laboratory result at private clinical chemistry laboratory in South Kalimantan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Background: Consumers of clinical laboratory sometimes wonder how to choose a laboratory, is it just based on speed, accuracy, and reliable results? The problem now is the awareness to quality control is still limited in regard to participation in the external quality control and not all has the appropriate internal quality control of the laboratory. Objective: This study was aimed to examine the quality of laboratory analysis result, accuracy and precision of laboratory analysis and the relationship between analytical internal quality control and accuracy and precision of laboratory analysis results. Methods: The measurement tools were questionnaires and gold standard. The analysis used t-test, Variance Index Score (VIS) and Spearman's Rank correlation. The pre-and post-analytical quality control were based on the score results categorized as good. Result: The test result F 0.05 showed that every laboratory was different in doing each pre-analytical (p=0.001) and analytical (p=0.002) tests. Meanwhile the post-analytical tests were not different (p=0.001). The metabolism test showed that in 55.6% laboratories the accuracy of analysis was good and the precision was 33.3%. The enzyme laboratory test (SGOT) with good accuracy result was 33.3% with 11.1% good precision. Accuracy and precision rank showed that there was negative relationship between analytical quality control and accuracy of analysis results of metabolite type (p=0.001) and enzyme type (p=0.023). The score of high analytical quality control was not balanced with high analysis result accuracy. There was no relationship between analytical quality control and precision of laboratory analysis result. The chemical laboratory analysis result of clinics that was very good was 33.3%, good 22.2% and average 22.2% and poor 22.2%. the clinical laboratory with poor category had relatively many patients and analysis staff and one of the laboratories had a staff in charge with clinical pathology background. Conclusion: The score of chemical laboratory quality control of private clinics in South Kalimantan in the pre-analytical, analytical and post-analytical stages were included in the category of good. The accuracy and precision of laboratory analysis result was better at the metabolite check up than that of enzyme (SGOT). There was relationship between the score of analytical quality control and that of laboratory analysis result which tend to be lower. There was no relationship between the score of analytical quality control and precision laboratory analysis result, both for metabolite and enzyme types. Every laboratory should include the level of precision reached and appoint staff doing the laboratory internal quality control.